Multi-objective topology optimization of a vehicle door using multiple material tailor-welded blank (TWB) technology. (October 2018) - Sun, Guangyong; Tan, Dongdong; Lv, Xiaojiang; Yan, Xiaolei; Li, Qing; Huang, Xiaodong
Highlights: The multi-objective multi-material optimization approach based on BESO is proposed. The proposed method is first applied to the optimization of TWB door panels. The study provides the design guidance for lightweight and multi-material TWB structures. Abstract: As one of effective technologies, tailor welded blank (TWB) has been extensively applied to improve structural performance and efficiency of material usage for lightweight automobile. The vehicle door is an important part of structure that presents many design requirements including stiffness, natural frequency, etc. However, finding an optimal layout of the multi-material TWB welding lines of a vehicle door remains fairly challenging through conventional design methods. This study proposed a multi-objective topology optimization method for this purpose. The compromise programming approach (CAP) coupled with the mean frequency method (MFM) is introduced to handle the multi-objective optimization involving stiffness and natural frequency criteria for multiple load cases. The multi-objective problems are then solved by the extended bi-directional evolutionary structural optimization (BESO) method. The design examples demonstrate that the proposed approach is suitable for the multi-objective and multi-material topology optimization (MMTO) of TWB indoor panel. The study also provides the design guidance for lightweight and multi-material structures with the TWB technology.